Intake of up to 3 Eggs per Day Is Associated with Changes in HDL Function and Increased Plasma Antioxidants in Healthy, Young Adults. Issue 3 (11th January 2017) - DiMarco, Diana M; Norris, Gregory H; Millar, Courtney L; Blesso, Christopher N; Fernandez, Maria Luz
Abstract: Background: HDL function may be more important than HDL concentration in determining risk for cardiovascular disease. In addition, HDL is a carrier of carotenoids and antioxidant enzymes, which protect HDL and LDL particles against oxidation. Objective: The goal of this study was to determine the impact of consuming 0–3 eggs/d on LDL and HDL particle size, HDL function, and plasma antioxidants in a young, healthy population. Methods: Thirty-eight healthy men and women [age 18–30 y, body mass index (in kg/m 2 ) 18.5–29.9] participated in this 14-wk crossover intervention. Subjects underwent a 2-wk washout (0 eggs/d) followed by sequentially increasing intake of 1, 2, and 3 eggs/d for 4 wk each. After each period, fasting blood was collected for analysis of lipoprotein subfractions, plasma apolipoprotein (apo) concentration, lutein and zeaxanthin concentration, and activities of lecithin-cholesterol acyltransferase, cholesteryl ester transfer protein, and paraoxonase-1. Results: Compared with intake of 0 eggs/d, consuming 1–3 eggs/d resulted in increased large-LDL (21–37%) and large-HDL (6–13%) particle concentrations, plasma apoAI (9–15%), and lecithin-cholesterol acyltransferase activity (5–15%) ( P < 0.05 for all biomarkers). Intake of 2–3 eggs/d also promoted an 11% increase in apoAII ( P < 0.05) and a 20–31% increase in plasma lutein and zeaxanthin ( P < 0.05), whereas intake of 3 eggs/d resulted in a 9–16% increase in serum paraoxonase-1 activity compared with intake of 1–2 eggs/d ( P < 0.05). Egg intake did not affect cholesteryl ester transfer protein activity. Conclusions: Intake of 1 egg/d was sufficient to increase HDL function and large-LDL particle concentration; however, intake of 2–3 eggs/d supported greater improvements in HDL function as well as increased plasma carotenoids. Overall, intake of ≤3 eggs/d favored a less atherogenic LDL particle profile, improved HDL function, and increased plasma antioxidants in young, healthy adults. This trial was registered at clinicaltrials.gov as NCT02531958.